Prehospital blood transfusion: experience from a specialized prehospital response vehicle : a retrospective cohort study - Weilbacher, Frank; Postina, Jens; Kaltschmidt, Nikolai; Kofler, Othmar; Dietrich, Maximilian; Leo, Albrecht; Weigand, Markus A.; Popp, Erik; Katzenschlager, Stephan (Frontiers in medicine, 2025)
BackgroundThis study evaluates the use and clinical implications of prehospital packed red blood cells administered by a specialized physician-staffed Medical Intervention Car in a German emergency medical service system capable of advanced interventions such as thoracotomy and extracorporeal cardiopulmonary resuscitation.MethodsWe conducted a retrospective cohort study of all prehospital patients treated with at least one unit of packed red blood cells (pRBC) by the MIC team between August 2019 and September 2024. In the trauma cohort, we compared characteristics and interventions between those who were admitted to the hospital and those for whom resuscitation was commenced on scene. For in-hospital comparisons, patients were grouped into two categories: those who continued to receive pRBCs and those who did not. A modified blood transfusion need score (mBTNS) was retrospectively applied to assess the clinical appropriateness of transfusion.ResultsA total of 57 patients received pRBCs, including 45 with traumatic and 12 with non-traumatic hemorrhage. Among trauma patients, 78% were male, 49% sustained penetrating injuries, and 56% were in traumatic cardiac arrest. There were higher rates of primary dispatch by the dispatch center in patients admitted to the hospital (43% vs. 13%; p = 0.048). The mean number of prehospital pRBC units transfused did not differ between those admitted and those for whom resuscitation was commenced (mean 4 [2]). Patients admitted to the hospital received fibrinogen (90% vs. 47%; p = 0.003), tranexamic acid (93% vs. 47%; p < 0.001), and Calcium (67% vs. 33%; p = 0.028) significantly more often compared to those who died on the scene. A lower pH and higher glucose level were significantly linked to continuous pRBC transfusion during the first 24 h after hospital admission. In the non-trauma cohort, gastrointestinal bleeding was the predominant cause (54%).ConclusionPrehospital transfusion by a trained MIC team led to high survival rates in trauma and non-trauma patients. The frequent invasive procedures underline the need for integrated prehospital blood transfusion within advanced care. Broader adoption of structured protocols in high-acuity systems warrants prospective evaluation.